PEMIKIRAN FILOSOFIS PANCASILA DALAM PENGELOLAAN SUMBER DAYA PERIKANAN - Yasser Arafat (Fakultas Hukum Universitas Borneo Tarakan, 2022)
AbstractThis research was conducted to find out philosophical thoughts about the values of Pancasila and the concept of fisheries resource management based on philosophical thoughts about the values of Pancasila.This type of research is a normative juridical research. The approach used in this research is the approach to applying the law and the conceptual approach.The results obtained from this study are that philosophical thinking about the values of Pancasila on a problem must involve the five principles of Pancasila. The philosophical thought of Pancasila in natural resource management is that it must preserve the paradigm that fishery resources are obligatory to achieve the welfare and prosperity of the people, management of fishery resources must be carried out in a fair and civilized manner now and in the future to be able to enjoy fishery resources so that they are available. In addition, civilized law is needed, involving community participation as the original owner of the right to fishery resources, and state control over fishery resources must be interpreted solely to achieve people's welfare and prosperity. Keywords: Pancasila, Fishery Resources, Management,